Comparative evaluation of healing after gingivectomy with electrocautery and laser - Praveen Kumar; Vidya Rattan; Sachin Rai (Elsevier, 2015)
Purpose of the study: To evaluate whether laser has got any advantage over electrocautery in performing gingivectomy procedure. Method: This was randomized split mouth prospective study where 17 patients having symmetrical gingival hyperplasia were treated with electrocautery and laser on each side. Intra- and postoperative parameters assessed were duration of surgery, bleeding, tissue sticking, postoperative pain and healing. The results were statistically analyzed and compared. Result: There were 7 Females and 10 Males with a mean age of 28.2 ± 11.6 years. The mean time taken on the laser and electrocautery was 16 (±8.05) and 16.7 min (±9.86) respectively and the difference was not significant. On laser side, there was no bleeding in 3 (17.6%) and self limiting in 14 patients (82.4%) whereas electrocautery side, there was no bleeding in 2 (11.8%) and self limiting in 15 patients (88.2%). Both electrocautery and laser were comparable regarding ease of use during gingivectomy procedure. Charring was observed on both sides although there was more charring on the laser side. Fibrinous slough was present on both sides at 24 h. Difference in healing was not significant at various time intervals. There were no significant difference in postoperative pain experienced by the patients among the laser and cautery group at different time intervals. Conclusion: Both techniques with proper adhesion to safeguards, can be used to remove gingival overgrowth with equal efficiency and wound healing capacity. There is no advantage of diode laser over electrocautery in performing gingivectomy.